Multi-echo investigations of positive and negative CBF and concomitant BOLD changes - Ratnamanjuri Devi; Jöran Lepsien; Kathrin Lorenz; Torsten Schlumm; Toralf Mildner; Harald E. Möller (NeuroImage, 2022)
Unlike the positive blood oxygenation level-dependent (BOLD) response (PBR), commonly taken as an indication of an ‘activated’ brain region, the physiological origin of negative BOLD signal changes (i.e. a negative BOLD response, NBR), also referred to as ‘deactivation’ is still being debated. In this work, an attempt was made to gain a better understanding of the underlying mechanism by obtaining a comprehensive measure of the contributing cerebral blood flow (CBF) and its relationship to the NBR in the human visual cortex, in comparison to a simultaneously induced PBR in surrounding visual regions. To overcome the low signal-to-noise ratio (SNR) of CBF measurements, a newly developed multi-echo version of a center-out echo planar-imaging (EPI) readout was employed with pseudo-continuous arterial spin labeling (pCASL). It achieved very short echo and inter-echo times and facilitated a simultaneous detection of functional CBF and BOLD changes at 3 T with improved sensitivity. Evaluations of the absolute and relative changes of CBF and the effective transverse relaxation rate, R2*, the coupling ratios, and their dependence on CBF at rest, CBFrest, indicated differences between activated and deactivated regions. Analysis of the shape of the respective functional responses also revealed faster negative responses with more pronounced post-stimulus transients. Resulting differences in the flow-metabolism coupling ratios were further examined for potential distinctions in the underlying neuronal contributions.